RANCANG BANGUN PROTOTYPE TURBIN KAPLAN SKALA PLTMH - Made Andi Kusumayana B; I Wayan Arta Wijaya; I Gusti Ngurah Janardana (Program Studi Teknik Elektro UNUD, 2021)
PLTMH is a type of generator that utilizes water resources for its workings. Utilization ofwater resources is still minimally carried out by the community, especially by students ofElectrical Engineering at Udayana University because it must be implemented directly on alarge enough river flow so that it is difficult to study. So, in this study, a prototype modeling ofMHP using a Kaplan turbine was designed which is useful for the learning process before beingimplemented directly in the river. The Kaplan turbine prototype is designed with a head of 2 m,an input pipe of 2xdimxand a discharge of 12 L/s, has a total of 30 guide blades,xwith an openingangle of 30o, with a lengthxofx0.05 meters, a widthxof 0.045 meters, an inside diameterxofx0.33metersxandxan outerxdiameterxofx0.42 meters. Thisxprototype has a total of 5 driving blades,withxanxouter diameterxofx0.16xmeters, a shaft neck diameterxof 0.06 meters, xaxrunner widthofx0.05 meters. The resultsxofxthe Kaplan turbine prototype test are able to produce axpowerxof3.64xwatts, a torquexofx0.231xNm, andxanxefficiencyxof 1.54%.